Assembling covalent organic framework membranes with superior ion exchange capacity - Wang, Xiaoyao; Shi, Benbing; Yang, Hao; Guan, Jingyuan; Liang, Xu; Fan, Chunyang; You, Xinda; Wang, Yanan; Zhang, Zhe; Wu, Hong; Cheng, Tao; Zhang, Runnan; et al. (Nature communications, 2022)
Ionic covalent organic framework membranes (iCOFMs) hold great promise in ion conduction-relevant applications because the high content and monodispersed ionic groups could afford superior ion conduction. The key to push the upper limit of ion conductivity is to maximize the ion exchange capacity (IEC). Here, we explore iCOFMs with a superhigh ion exchange capacity of 4.6 mmol g −1 , using a dual-activation interfacial polymerization strategy. Fukui function is employed as a descriptor of monomer reactivity. We use Brønsted acid to activate aldehyde monomers in organic phase and Brønsted base to activate ionic amine monomers in water phase. After the dual-activation, the reaction between aldehyde monomer and amine monomer at the water-organic interface is significantly accelerated, leading to iCOFMs with high crystallinity. The resultant iCOFMs display a prominent proton conductivity up to 0.66 S cm −1 , holding great promise in ion transport and ionic separation applications. Covalent organic framework-based membranes are highly tunable materials with potential use in a variety of applications. Here the authors report a dual-activation interfacial polymerization strategy to prepare ionic covalent organic framework membranes with high ion exchange capacity.